Analisis Kepuasan Penumpang Atas Kualitas Layanan Jasa CV. Indah Travel Terayek Tembilahan – Pekanbaru - Gea Wilvi Onalza; Sri Restuti; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to find out the level of passenger satisfaction for the quality of service which includes tangible, reliability, responsiveness, assurance, andempathy on the CV. Indah Travel route of Tembilahan - Pekanbaru. This study uses Importance - Performance Analysis with Cartesian diagram. In this study, the populations were all passengers of CV. Indah Travel route of Tembilahan - Pekanbaru, which made 100 respondents who were sampled by Purposive Sampling Method that is taking samples to passengers with a minimum of 3 timeshave used the services of CV. Indah Travel. From the research and discussion of the analysis of satisfaction,then gained the value of variablefrom passenger satisfaction over the quality of the service -dimensional tangible / physical evidence amounted equal to 77.98 %, the dimensions of reliability of 66.41 %, dimensions responsiveness of 76.97 %, the dimension of assurance of 65 , 97 % and dimensions of empathy of 77.19 % . From the results of Importance and Performance Analysis (IPA), can be seen that the total average of all indicators of the five (5) service dimensions is 3.25 < 4.46 (P < E). It means the passengers are not satisfied with the service provided which is expectation exceed the performance.Keywords: Quality of Service and Passenger Satisfaction